[OP.1A.04] PLASMA SODIUM CONCENTRATION AND THE RISK OF CARDIOVASCULAR DISEASE: A LARGE COMMUNITY-BASED COHORT STUDY. (September 2017) - Cole, N.; De Lusignan, S.; Swift, P.; He, F.; Jones, S.; Hinton, W.; Hayward, N.; Van Vlymen, J.; Arrowsmith, B.; Suckling, R.
Abstract : Objective: Reducing dietary salt lowers both blood pressure and cardiovascular risk. The mechanisms underlying the adverse effects of high salt intake are incompletely understood, but parallel increases in plasma sodium (PNa) may be of importance: observational and experimental studies have identified that small increases in PNa are associated with increased blood pressure and changes to endothelial function, independent of changes in plasma volume. However, very few studies have investigated whether there is an association between PNa and cardiovascular disease (CVD). Design and method: This was a retrospective cohort study using the Royal College of General Practitioners Research and Surveillance Centre database. Data collected between April 2005 –March 2015 was extracted, and the baseline period was defined as before April 2010. The primary outcome was incident CVD (myocardial infarction, acute coronary syndrome, coronary revascularisation, stroke or heart failure diagnosis) during the 5-year follow-up period. Exclusion criteria were: age less than 40, diabetes mellitus, prior CVD event, end-stage renal disease and liver cirrhosis. Baseline PNa was determined using the most recent laboratory result, and a mean was calculated if a second result was available at least 3 months apart. Results: 234, 764 individuals were included in the study. A PNa of 137 mmol/L or less at baseline was associated with increasing age, female gender, hypertension, and prescription of cardiovascular medications including diuretics. After multivariate adjustment for confounding factors, there was a significant 'J-shaped' relationship between PNa and CVD (Figure 1). No linear association between increased PNa and blood pressure was demonstrated. Figure. No caption available. Conclusions: To our knowledge, this is the largest study to investigate the relationship between PNa and CVD. The association was greatest with lower PNa, and was such that the risk increased at concentrations well within the normal physiological range (140 mmol/L or less). One hypothesis is that lower PNa is an indicator of neurohormonal activation prior to the development of overt CVD. A lower PNa may be a useful indicator for the future development of CVD but obscure the potential importance of high PNa over longer periods of time.